Influência do uso de alta rotação elétrica em cirurgias de terceiros molares inferiores: estudo clínico randomizado, prospectivo e “boca dividida” - Sol, Izabella [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
A cirurgia de exodontia de terceiros molares está relacionada a transtornos pós-operatórios gerados pelo trauma tecidual. O objetivo deste estudo clínico randomizado “boca dividida” é avaliar os efeitos clínicos, histológicos e o reparo alveolar após utilização da alta rotação pneumática e elétrica na exodontia de terceiros molares inferiores. Dezesseis pacientes foram submetidos a exodontia dos dois terceiros molares inferiores com intervalo mínimo de 15 dias. Em um dos lados foi utilizada a alta rotação pneumática (Grupo C) e no outro lado foi utilizada alta rotação elétrica (Grupo E). Foram avaliados tempo cirúrgico, dor, edema e trismo pós-operatórios (1, 3 e 7 dias), qualidade de vida, dano ósseo periférico por histologia e reparo ósseo alveolar pós-operatório. O grupo GE permitiu menor tempo operatório (p=0,019), menor dor (p=0,034), menor edema (p<0,001) e menor trismo (p=0,025) no 1° dia pós-operatório; menor dor (p=0,034) e trismo (p=0,010) no 3° dia pós-operatório e menor trismo (p=0,032) no 7° dia pós-operatório e melhor qualidade de vida (p=0,007). Não foram observadas diferenças em relação ao dano ósseo periférico (p=0,298) e densidade óssea do reparo alveolar aos 2 (p=0,916) e 4 meses (0,210), comparados GC e GE. A alta rotação elétrica fornece melhores parâmetros clínicos pós-operatórios de dor, edema e trismo quando comparada com alta rotação pneumática na cirurgia dos terceiros molares inferiores.

The medication-related osteonecrosis of the jaws (MRONJ) is a pathological condition that is difficult to treat. Therefore, the ideal conduct is establishment of strategies aimed at preventing its ocurrence. Topical therapy with active oxygen-releasing gel (TTAORG) and the antimicrobial photodynamic therapy (aPDT) have antimicrobial activity and biomodulation action, which makes them potencial preventive strategies to MRONJ. The aim of this study was to evaluate the effectiveness of TTAORG in association with aPDT in the alveolar repair in senescent female rats treated with oncological dose of zoledronate and to analyze its potention in preventing the occurence of MRONJ. Twenty-eight senescent female rats were divided in four experimental groups: NLT, TTAORG, aPDT, TTAORG+aPDT. On 0 day a ligature was installed around the mandibular first molar on the left side to induce experimental periodontitis. From day 1 to 50, the rats received, every three days, 0.45 ml of zoledronate (100 μg/Kg), intraperitoneally. After three weeks of treatment with zoledronate, the mandibular first molar on the left side was extracted. In the NLT group (n=7) no local treatment was performed. In the TTAORG group (n=7) and in the aPDT group (n=7) the socket was submitted to three sessions of TTAORG and aPDT, respectively. In the TTAORG+aPDT group (n=7) the socket was submitted to three sessions of TTAORG followed by aPDT. Local treatments were performed at 0, 2 and 4 days after dental extraction. Euthanasia was performed 28 days after dental extraction. The hemimandibles were processed to allow: histological analysis, histometrical analysis of the percentage of newly formed bone tissue (NFBT) and non-vital bone tissue (NVBT) and immunohistochemical analysis (BMP2/4, morfogenetic bone protein 2/4 and; OCN, osteocalcin). The NLT group showed a great impairment of tissue repair process. The TTAORG, aPDT and TTAORG+aPDT groups showed a favorable tissue repair at the dental extraction site. In the NLT group, the percentage of NFBT was lower, while the percentage of NVBT was higher than the other groups. The TTAORG group showed lower percentage of NFBT and a higher percentage of NVBT when compared with the aPDT and TTAORG+aPDT groups. In the TTAORG+aPDT group the percentage of NFBT was higher than aPDT group. The TTAORG+aPDT group showed the highest pattern of immunolabeling for BMP2/4 and OCN. TTAORG, aPDT and TTAORG+aPDT were able to avoid the occurence of MRONJ after dental extraction with differents levels of effectiveness. As a monotherapy, aPDT was better than TTAORG, but, the greatest effectiveness was obtained with the use of TTAORG+aPDT.
The influence of electrical high-speed rotation on mandibular third molar surgeries: a prospective, randomized, split-mouth clinical and radiographic study
Keywords: Regeneração óssea; Osteotomia; Dente serotino; Osteonecrose; Extração dentária; Tooth extraction